Integrated pyroptosis measurement and metabolomics to elucidate the effect and mechanism of tangzhiqing on atherosclerosis - Chen, Rui; Chen, Ting; Zhou, Zhihuan; Song, Zhihui; Feng, Wanying; Yang, Xintong; Wang, Xianliang; Li, Bin; Ding, Xinya; Zhang, Han; Wang, Yi (Frontiers in Physiology, 2022)
Tangzhiqing formula (TZQ) is a traditional Chinese medicine prescribed to treat glucose and lipid metabolism disorders. Extensive work has shown that TZQ has a significant effect on diabetes and hyperlipidemia, but its effect on atherosclerosis (AS) is unclear. This study combines pyroptosis with metabolomics to elucidate the effect and mechanism of TZQ on AS. ApoE-/- mice fed a high-fat diet for 8 weeks (AS mice) were used as a model of AS. After 6 weeks of atorvastatin or TZQ treatment, aortic lumen diameter, aortic lesion size, serum lipid profile, cytokines, and Nod-like receptor protein 3 (NLRP3) inflammasome-mediated pyroptosis were analyzed. Serum metabolomics profiles were obtained to examine the effect of TZQ on AS and the correlation between pyroptosis and metabolites was further analyzed. TZQ significantly reduced the diameter of the common carotid artery during diastole and the blood flow velocity in the aorta during systole; reduced blood lipid levels, arterial vascular plaques, and the release of inflammatory cytokines; and inhibited the NLRP3 inflammasome-mediated pyroptosis. According to metabolomics profiling, TZQ is engaged in the treatment of AS via altering arachidonic acid metabolism, glycerophospholipid metabolism, steroid hormone production, and unsaturated fatty acid biosynthesis. The cytochrome P450 enzyme family and cyclooxygenase 2 (COX-2) are two major metabolic enzymes associated with pyroptosis. Our results indicate that TZQ prevents AS by regulating metabolism and the expression and of the cytochrome P450 enzyme family and cyclooxygenase 2 to inhibit pyroptosis.